Effect of a Proposed Training Program Using Visual Feedback to Develop Skill Performance Levels in Floor Gymnastics Exercises - Atheer Hamza Jeegan Joqli (Journal of Education and Sport Science, 2026)
Objectives: This study aimed to examine the effect of a proposed training program using visual feedback on improving skill performance in floor gymnastics exercises among students of the College of Physical Education and Sports Sciences. Materials and Methods: This study used an experimental design with two equivalent groups, namely an experimental group and a control group, through pre- and post-test measurements. The sample consisted of 30 students who were randomly divided into two equal groups. The experimental group followed a 12-week visual feedback-based training program with three training units per week, while the control group continued with the traditional training program. Skill and physical performance tests were used to measure students’ floor gymnastics performance. The data were analyzed using SPSS. Results: The results showed statistically significant differences between the pre-test and post-test in favor of the experimental group at the 0.05 significance level. The experimental group also achieved better post-test results than the control group, indicating that the visual feedback-based training program contributed positively to improving floor gymnastics skill performance. Conclusions: The proposed training program using visual feedback was effective in developing students’ skill performance in floor gymnastics exercises. Visual feedback can be used by lecturers and coaches as a practical training strategy to help students recognize movement errors, improve technical execution, and achieve better performance outcomes.